Pro-Poor Growth: A Primer - Ravallion, Martin (World Bank, Washington, D.C., 2013)
These days it seems that almost everyone in the development community is talking about "pro-poor growth." What exactly is it, and how can we measure it? Is ordinary economic growth always "pro-poor growth" or is that some special kind of growth? And if it is something special, what makes it happen? The author first reviews alternative approaches to defining and measuring "pro-poor growth." He then analyzes evidence on whether growth is pro-poor, what factors make it more pro-poor (including the role played by both initial inequality and changing inequality), and whether the factors that make the distribution of the gains from growth pro-poor come at a cost to growth. The author identifies some priorities for future research.